Surrender my love - Lindsey, Johanna (Lindsey, Johanna. Viking., 1994)
Wrongly branded a spy, the dark Viking lord Selig Haardrad suffered greatly in the dungeons of Lady Erika of Gronwood. But one thought sustained him throughout is torment: revenge! Now Destiny's great wheel has turned--and Selig's exquisite, honey-haired tormentor has been delivered into the Norseman's hands. Now it is Selig who is the master, bound and determined to break the proud spirit of his captive "ice queen" and to conquer her with passions sword--never dreaming that his own heart will be vanquished by sensuous desire ... and victorious love